KARAKTERISTIK SENSORIS DAN KIMIA BUMBU INSTAN DARI FORMULASI BUMBU HERBAL MENGGUNAKAN MALTODEKSTRIN DAN TWEEN 80 PADA PROSES PENGERINGAN - Eva Mayasari; Jessi Manalu (Universitas PGRI Semarang, 2019)
The study was aimed determining the best sensory characteristic on herb seasoning extract with the concentration vary salt added and determined of maltodextrin and tween 80 added on leaf of instant herbs seasoning using foam mat drying method. This study used a Completely Randomized Design (CRD) which is (1) salt concentration; 0,4%, 0,6% and 0,8%, (2) concentration of maltodextrin and tween 80; 5:0,5% ; 10:0,5% ; 15:0,5% ; 5:1% ; 10:1% ; 15:1%. The observed parameters in this study were sensory characteristics statistically using ANOVA (α=5%) and Duncan (α=5%). The results showed that the higher of concentration salt on formulation seasoning herb extract the higher panelists' preference. The treatment of 5% maltodextrin and 1% tween 80 was the best treatment of instant herbs seasoning based on panelists preference. The sensory value were aroma of 4,4 (neutral) and taste of 4.8 (slightly like).